ملاحظات أولية حول المجمعات القاعية والسمكية على الساحل السوري (منطقة اللاذقية). التنوع الحيوي المحلي والمهاجر - بيطار, غازي (Latakia University Journal -Biological Sciences Series, 2018)
في إطار معاهدة التعاون الثقافي بين لبنان وسورية تتم حالياً دراسة التنوع الحيوي (القاعي والسمكي) المتواجد على الشواطئ اللبنانية والسورية. ففي هذا البحث المتعلق فقط بالساحل السوري يتطرق الباحث، استناداً إلى عمليات الغوص، إلى توزع المجمعات الحيوانية والنباتية القاعية حسب تسلسلها ومستوى وجودها على القاع الصخري خصوصاً وذلك انطلاقاً من سطح الماء، حيث توجد المصاطب الفيرمية، حتى الأعماق التي تتواجد عليها الأعشاب ظاهرات الإلقاح Phanerogams وبالأخص النوعCymodocea nodosa من وحيدات الفلقة (Monocotyledons). ويتضمن البحث نبذة عن التركيب النوعي للأسماك الذي شوهد في عين المكان ويلقي الضؤ على التنوع الحيوي المحلي وعلى الأنواع المهاجرة (أو الليسيبسيانية) (Lesssepsian species) من المحيط الهندي والهادي نحو البحر الأبيض المتوسط مروراً بالبحر الأحمر وعبوراً بقناة السويس. كما أنه يركز على أثر بعض الأنواع المهاجرة "الغازية" كالطحلب الأسمر Stypopodium schimperi والطحلب الأحمر Galaxaura rugosa على الأنواع المحلية. Within the frame of the Cultural Agreement between Lebanon and Syria, a study of biodiversity (benthos & fish) along the Lebanese-Syrian coast is currently undertaken. In the present paper which is only limited to the Syrian side, the researcher, who depend on the results of diving, points out to the distribution of the benthic animal and vegetal communities according to their appearance sequence and level of occurrence -mainly on the rocky substratum- starting from the vermetids platforms of the water surface to the bottoms where the phanerogams occur, in particular the Monocotyledon Cymodocea nodosa. The paper includes a briefing on the specific composition of the ichtyofauna that was found in the same place and highlights the local biodiversity and the migratory species (lessepsians) from the Indo-pacific to the Mediterranean, throughout the Red sea and the canal of Suez. In addition, the paper focuses on the impact of some invasive migratory species such as the brown algae Stypopodium schimperi and the red algae Galaxaura rugosa on the local species.